2019
DOI: 10.1158/1078-0432.ccr-18-3412
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD38 Enhances the Antileukemic Activity of Ibrutinib in Chronic Lymphocytic Leukemia

Abstract: Purpose: CD38 has emerged as a high-impact therapeutic target in multiple myeloma, with the approval of daratumumab (anti-CD38 monoclonal antibody). The clinical importance of CD38 in chronic lymphocytic leukemia (CLL) patients has been known for over two decades, though it’s relevance as a therapeutic target in CLL remains understudied. Experimental Design: We investigated the biological effects and anti-tumor mechanisms engaged by daratumumab in primary CLL cells. Besides its known immune-effector mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Finally, it impedes adhesion to VCAM-1 by down-regulating matrix metalloproteinases, therefore inhibiting tumor infiltration and dissemination. Such findings were confirmed by Manna et al [86], who also detected apoptosis when CLL cells were exposed to Daratumumab. The same research group also detected a CD38-mediated down-regulating of BTK, and demonstrated that accordingly, Daratumumab administration enhances Ibrutinib anti-tumoral activity.…”
Section: Therapeutic Implications: Daratumumab As Monotherapy or Combsupporting
confidence: 60%
“…Finally, it impedes adhesion to VCAM-1 by down-regulating matrix metalloproteinases, therefore inhibiting tumor infiltration and dissemination. Such findings were confirmed by Manna et al [86], who also detected apoptosis when CLL cells were exposed to Daratumumab. The same research group also detected a CD38-mediated down-regulating of BTK, and demonstrated that accordingly, Daratumumab administration enhances Ibrutinib anti-tumoral activity.…”
Section: Therapeutic Implications: Daratumumab As Monotherapy or Combsupporting
confidence: 60%
“…In hematology, different studies have shown that DARA may enhance macrophage-mediated phagocytosis of Burkitt’s lymphoma cells in vitro [ 60 ] and further enhance lysis by ADCC (Antibody-dependent cellular cytotoxicity) and ADCP (Antibody-dependent cellular phagocytosis) of CLL (Chronic lymphocytic leukemia) cells both in vitro and in vivo [ 61 , 62 , 63 ]. Moreover, in ex vivo peripheral blood cells from CLL patients (and in a CLL patient-derived xenograft model in vivo), DARA was noted to deplete the B-regulatory and T-regulatory cell fractions but promoted downstream activation and expansion of PD-1 low CD8 + cytotoxic T-cells.…”
Section: Clinical Applications Outside MMmentioning
confidence: 99%
“…CD19 1 CD5 1 CD38 hi/lo CLL cells and CD4 1 CD25 1 CD127 lo Tregs were sorted out using magnetic beads/flow-sorter (sorting and gating strategy in supplemental Materials and methods). 18 A CLL-patientderived xenograft (PDX) model was established, 22 using PBMCs isolated from a patient with CLL with CD38 1 disease, injected into NSG mice (The Jackson Laboratory). iTreg formation assays were carried out using naive Th cells prestimulated with anti-CD3 (5 mg/mL)/CD28 (5 mg/mL) antibodies followed by coculture with either autologous Breg-like (CD19 1 CD24 1 CD38 1 ) or non-Breg (CD19 1 CD24 1 CD38 2 ) CLL cells.…”
Section: Human Samples T-cell Assays Mouse Model and Statistical Amentioning
confidence: 99%
“…17 We have recently demonstrated that targeting CD38 with the anti-CD38 human monoclonal antibody (mAb) daratumumab downregulates B-cell receptor signaling and enhances the antitumor activity of ibrutinib in CLL cells and Waldenstrom macroglobulinemia tumor cells. 18,19 These investigations revealed that daratumumab induces antibodydependent cell-mediated cytotoxicity, complement-dependent cytotoxicity, antibody-dependent cellular phagocytosis, and direct apoptosis of CLL cells in vitro, and together these undergird its anti-CLL activity in vivo.…”
Section: Introductionmentioning
confidence: 99%